Integration of GIS Web Services - Paliulionis, Viktoras (Lietuvos matematikos rinkinys, 2008)
The number of GIS web services has been essentially increasing in recent years. The services encompass geospatial data providing and processing. GIS web services enable application developers to integrate GISfunctionality into their web applications without having to build the functionality or host the mapping data locally. The integration of services from different providers enables creating more sophisticated servicesand applications. This paper analyzes peculiarities of GIS web services, and discusses ways of their integrating. In order to investigate issues of implementing distributed GIS web services, a prototype of a system was designed and implemented. The system integrates public map services and our specialized GIS Akis-WS services. This paper describes specific features and architecture of this system.
Keywords: GIS; web services; integration